Equalization of MIMO Channels in LTE-Advanced - Sime, Tibebu Abebe (My University, 2012)
LTE-Advanced is one of the most evolving and competing standards that target the high speed 4G wireless communications. In order to meet the target of this new cellular technology developed under auspices of the 3GPP standardization bodies, it is necessary to ensure that this technology is able to provide the headline requirements recommended for the terrestrial components of the IMT-Advanced radio interface for 4G broadband mobile communications. One of the key radio technologies that will enable LTE-Advanced to achieve the high data throughput rates is the use of MIMO antennas that play an important role as the conventional communications like using more bandwidths and higher modulation types are limited. Together with this are the downlink OFDMA and the uplink SC-FDMA techniques that are employed to improve the system architecture burdened with the data rates rising pretty well above what was previously in use. The combination of these technologies will help LTE-Advanced keep pace with other wireless technologies that may be competing to offer very high data rates and high level of mobility. But achieving the high data rate up to 1 Gbits/s in 4G mobile networks over wide frequency bandwidths and recovering the original information without being corrupted and downgraded has been a daunting task for engineers. Thus, this paper will briefly discuss the performances of MIMO equalization techniques such as MMSE, ZF and ZF-SIC equalizers in a Rayleigh multichannel fading.
Keywords: LTE; LTE-Advanced; MIMO; Rayleigh channel; OFDMA; SC-FDMA; fi=Tietoliikennetekniikka|en=Telecommunications Engineering|; fi=Master's Degree Programme in Telecommunication Engineering|en=Master's Degree Programme in Telecommunication Engineering|